2005
DOI: 10.1659/0276-4741(2005)025[0147:tiocip]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Changes in Population, Land Use, and Land Management for Surface Runoff in the Upper Nile Basin Area of Ethiopia

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
220
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(232 citation statements)
references
References 5 publications
11
220
0
1
Order By: Relevance
“…Shiferaw [72] stated the reasons for changes in land use/cover were natural factors such as drought and climate change as well as human driving factors such as population growth, over intensification of farm sizes [76], and land tenure policies [77,78]. Zeleke et al [12] indicated an age-old tradition of clearing increasingly steeper land for cultivation and lack of appropriate land use policies, as reasons land use changes threatening soil degradation in North western Ethiopian highlands.…”
Section: Discussionmentioning
confidence: 99%
“…Shiferaw [72] stated the reasons for changes in land use/cover were natural factors such as drought and climate change as well as human driving factors such as population growth, over intensification of farm sizes [76], and land tenure policies [77,78]. Zeleke et al [12] indicated an age-old tradition of clearing increasingly steeper land for cultivation and lack of appropriate land use policies, as reasons land use changes threatening soil degradation in North western Ethiopian highlands.…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable agricultural practices are challenged by severe soil erosion, as it reduces on-farm soil productivity and causes food insecurity (Sonneveld et al, 2003;Moges and Holden, 2006;Bewket, 2007). In most developing countries, including Ethiopia, anthropogenic activities trigger soil erosion (Belyaev et al, 2004;Hurni et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1), the basin covers an area of 199,812 km 2 with significant contribution of runoff and fertile highland soil to Sudan and Egypt in the downstream. Biophysical and anthropogenic factors combined with torrential runoffs in the rugged highlands in the basin are causing considerable land degradation and soil erosion in the upstream, whereas deforestation is a major concern in the mid/low lands of the basin (Hurni et al 2005;Gebrehiwot et al 2014). Torrential runoff washing off the rugged terrains, poor land-use management has been reported as a cause for gully formation, soil erosion and land degradation threaten the livelihood of subsistence farmers Yalew et al 2012;Tekleab et al 2014).…”
Section: Introductionmentioning
confidence: 99%